2003
DOI: 10.1002/jcop.10042
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Russian transition on psychosocial resources and psychological distress

Abstract: ⅢStudies suggest that the difficult transition of the Russian economy has led to decreased physical health among Russians. However, the impact of economic turmoil on Russians' psychological health has not been examined. We used Hobfoll's (1988;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…Again, although resource loss was entered in the last step, it proved to be a robust predictor. This finding was consistent with the results of previous research in the literature, which reported that resource loss was related to psychological distress (Lane & Hobfoll, 1992;Shteyn, Schumm, Vodopianova, Hobfoll, & Lilly, 2003;Smith & Freedy, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…Again, although resource loss was entered in the last step, it proved to be a robust predictor. This finding was consistent with the results of previous research in the literature, which reported that resource loss was related to psychological distress (Lane & Hobfoll, 1992;Shteyn, Schumm, Vodopianova, Hobfoll, & Lilly, 2003;Smith & Freedy, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…However, no significant group differences were found for anxiety and stress symptoms, even though the values of the positive variables—described as significant predictors of anxiety and stress in earlier studies [41,81]–were higher in the Facebook user group. This speaks for the dual-factor model of mental health which describes two interrelated but separate unipolar mental health dimensions (positive and negative) [3537].…”
Section: Discussioncontrasting
confidence: 63%
“…To date, research assessing the impact of change has focused on the personal situation of individuals. For example, it has been shown that initiating numerous and fast‐paced organizational restructuring is accompanied by feelings of personal threat, distress, and job dissatisfaction (Hobfoll & Lilly, 1993; Kelly & Steed, 2004; Littler, Dunford, Bramble, & Hede, 1997; Morgan & Zeffane, 2003; Schmitt & Maes, 1998; Shteyn, Schumm, Vodopianova, Hobfoll, & Lilly, 2003; Slone, Kaminer, & Durrheim, 2002; Tsutsumi, Nagami, Morimoto, & Matoba, 2002). However, societal and organizational change not only affect individuals, but groups as well.…”
Section: Discussionmentioning
confidence: 99%